Investigating Relationships between Primary Schools’ Organizational Health and Teachers’ Organizational Trust - Esmahan Ağaoğlu; Damla Ayduğ (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This study was carried out to investigate the relationship between primary school teacher’s opinions about organizational health and their organizaitonal trust levels. In accordance with this purpose, primary school’s organizational health level based on teachers’ opinions and teachers’ organizational trust level were examined. The sample group of the study consisted of 912 teachers who work in primary schools depending on Tepebaşı and Odunpazarı District National Education Directorate during the fall semester of 2013-2014 academic year. The data were collected by Organizational Health Questionnaire for Primary Schools, Organizational Health Scale, and Personal Information Form. The data were analyzed using descriptive statistics and Pearson product-moment correlation analysis. With respect to results of the study, it was found that primary school teachers evaluated organizational health of their school high. According to the results, it was found that primary school teachers had high organizational trust level. Lastly, it was determined that there is a positive, strong and statistically meaningful relationship between organizational health of primary schools and organizational trust level of teachers. Based on the results of the study, it can be suggested that school-wide social activities could be organized to make schools healthier organizations and increase teachers’ trust level in colleagues, administrators and shareholders. In addition, with further researches, it can be examined organizational health and organizational trust concepts in terms of cause effect relationship.